Study of Cognitive Impairment and Existing Co-Morbidities Observed Among Geriatric Population in an Urban Slum - Pallavi S Shelke; Rupali R Rajput; Darshana R Kolte (Medsci Publications, 2019)
Background: Among vascular risk factors, chronic arterial hyper- tension is a major contributor to cognitive impairment. Hyperten- sion important risk factor for cerebrovascular pathology leading to stroke and dementia Objectives:1. To study certain risk factors of cognitive impairment and suspected dementia like hypertension, diabetes, ischemic heart disease, cerebro-vascular disease.2. To study the association of ad- diction with cognitive impairment and dementia. Methods: The study was community based descriptive study with cross sectional design. The period of study was from January 2005 to June 2006. Result: Prevalence of mild cognitive impairment and suspected de- mentia was 18.6% and 4.1% respectively. Out of the total 242 re- spondents 88 were known to have hypertension. They had higher proportion of cognitive impairment (26.2%). Conclusions: Known hypertensive's had higher proportion of cog- nitive impairment as compared to those with no history of hyper- tension. But the duration or treatment of hypertension was not found to be associated with cognitive status. The study showed no association of diabetes with the cognitive status. Individuals with cerebrovascular disease showed significantly higher proportion of cognitive impairment.